Indifference, indecisiveness, experimentation and stochastic choice - Efe A. Ok; Gerelt Tserenjigmid (Theoretical Economics, 2022)
Among the reasons behind the choice behavior of an individual taking a stochastic form are her potential indifference or indecisiveness between certain alternatives, and/or her willingness to experiment in the sense of occasionally deviating from choosing a best alternative in order to give a try to other options. We introduce methods of identifying if, and when, a stochastic choice model may be thought of as arising due to any one of these three reasons. Each of these methods furnishes a natural way of making deterministic welfare comparisons within any model that is rationalized as such. In turn, we apply these methods, and characterize the associated welfare orderings, in the case of several well-known classes of stochastic choice models.
Keywords: D01; D11; D81; D91; 330; Stochastic choice; indifference; incomplete preferences; experimentation; the general Luce model; random utility; additive perturbed utility; individual welfare